(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2025)
In a democracy, good governance is system of governance that is participatory, transparent, accountable, efficient, and equitable and follows the rule of law. In an election, the issue of good governance paves the way for all political parties to come to power and go out. Under good governance, responsibility, accountability and transparency of the system are the main aspects which show how successful a government has been in bringing up good governance. Before 2014, United Progressive Alliance (UPA) formed the government for two consecutive terms in which many issues like corruption, inflation, violence against women and unemployment emerged as the main issues of the people which became the basis for change of power in the 2014 election and Bhartiya Janata Party, turned the election result in its favor by promising good governance. National Democratic Alliance (NDA) formed the government and worked on many issues which were supported by the public viz., Ram Mandir, Triple Talaq and Article 370 etc. But corruption, inflation, crimes against women, misuse of constitutional institutions for self-motivated interests was on rise. Both opposition and voters criticize the ruling party as they wanted socio economic upliftment and employment opportunities for all. The Lok Sabha election 2024 gave mandate for strong democracy and vocal opposition due to the deteriorating condition of democracy. The main issue regarding the protection of the constitution was of prime concern for them. In this research paper, an attempt has been made to analyze the election result of 2024 for good governance and strong democracy.